Campus virtual tour: Exploring the potentials for Malaysian Universities / Mazliana Hasnan … [et al.] - Hasnan, Mazliana; Abu Hashim, Anis Hasliza; Eelco, De Vries; Ariffin, Kamisah (Universiti Teknologi MARA Cawangan Pahang, 2009)
Many international universities have now shifted from using text and still images to display information to providing virtual tour of the campus in their websites. The tour enables users to explore the selected locations with the images navigable at their own pace. This paper explores the potentials of employing such approach for Malaysian universities. A prototype of a local campus virtual tour was developed to evaluate the effectiveness of the approach. The results of user evaluation reveal that the experience of touring the campus virtually has great potentials as the lour is claimed as cost saving. convenient and can have long and lasting impact on the users.